Resin composition and application thereof

By using the resin composition of surface-treated titanate and nitride filler and maleimide resin combined with surface-treated resin in 5G mobile communication system, the challenge of improving the heat dissipation performance and dielectric constant of the substrate material is solved, and high efficiency is achieved Thermal management and electromagnetic performance improvement.

CN119391180APending Publication Date: 2025-02-07SHENGYI TECH SUZHOU

Patent Information

Application Number
CN202411501185.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In 5G mobile communication systems, the development of high-frequency high-speed circuits and 5G millimeter-wave antenna modules faces the challenge of improved thermal performance and dielectric constant of substrate materials, resulting in a decrease in communication speed and quality.

Method used

A resin composition is adopted, including maleimide resin, titanate compounds and fillers such as aluminum nitride, silicon nitride or boron nitride, and surface treatment is carried out by an anhydride-based silane coupling agent to improve the filler compatibility and performance.

Benefits of technology

While maintaining high heat resistance and bonding, the resin composition improves thermal conductivity and dielectric constant, and meets the requirements of high heat resistance, high adhesion, high Dk and high thermal conductivity of the 5G mmWave antenna module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103844740000022
    Figure BDA0005103844740000022
  • Figure BDA0005103844740000031
    Figure BDA0005103844740000031
  • Figure BDA0005103844740000034
    Figure BDA0005103844740000034
Patent Text Reader

Abstract

The present invention provides a resin composition comprising: 50-100 parts by weight of a maleimide resin; 10-80 parts by weight of a first filler, wherein the first filler is a titanate compound; 10-100 parts by weight of a second filler, wherein the second filler is at least one of aluminum nitride, silicon nitride or boron nitride; the first filler or / and the second filler is / are subjected to surface treatment by using an anhydride-based silane coupling agent; according to the present invention, the compatibility among the first filler, the second filler and the maleimide resin can be improved, and the high heat resistance and the high adhesion can be maintained so as to obtain the cured product with characteristics of excellent heat resistance, excellent adhesion, excellent thermal conductivity and stable high Dk value, such that the cured product with excellent comprehensive performance can be obtained, and the obtained cured product has characteristics of good heat resistance, good adhesion and good thermal conductivity. And the requirements of high heat resistance, high cohesiveness, high Dk and high thermal conductivity of the 5G millimeter wave antenna module are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and in particular to a resin composition and application thereof. Background Art

[0002] In recent years, with the popularization of smartphone terminals and the rapid development of technologies such as IoT (Internet of Things), the number of home appliances and electronic devices with wireless communication functions has continued to increase, resulting in an increase in wireless network communication volume and a decrease in communication speed and quality. To solve this problem, in 5G mobile communication systems, multiple antenna elements are used for higher beamforming and spatial multiplexing, while using higher frequency micrometer wave signals.

[0003] As electronic circuits become increasingly demanding in terms of speed, thinness, and miniaturization, the development of electronic devices presents characteristics such as high power and high density. The heat dissipation performance of the carrier-substrate material of electronic components is becoming increasingly important, especially in copper-clad laminates suitable for high-frequency and high-speed circuits. At the same time, in order to achieve the miniaturization of 5G millimeter-wave antenna modules, it is also necessary to increase the dielectric constant (Dk) of the substrate. Summary of the invention

[0004] The purpose of the present invention is to provide a resin composition and application thereof.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a resin composition, comprising:

[0006] Maleimide resin: 50-100 parts by weight;

[0007] First filler: 10-80 parts by weight, wherein the first filler is a titanate compound;

[0008] Second filler: 10-100 parts by weight, the second filler is at least one of aluminum nitride, silicon nitride or boron nitride;

[0009] The first filler and / or the second filler are surface treated with an anhydride-based silane coupling agent.

[0010] As a further improvement of the present invention, the weight ratio of the first filler to the second filler is 0.3-5.

[0011] As a further improvement of the present invention, the first filler is at least one of calcium titanate, barium titanate, strontium titanate, lead titanate, magnesium titanate, lanthanum titanate, neodymium titanate, barium neodymium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

[0012] As a further improvement of the present invention, the average particle size of the first filler is 0.1-5 μm, and the average particle size of the second filler is 3-20 μm.

[0013] As a further improvement of the present invention, the average particle size of the second filler is larger than the average particle size of the first filler.

[0014] As a further improvement of the present invention, the structural formula of the anhydride-based silane coupling agent is:

[0015] Among them, the R group is a C1-C5 alkyl group, and R1 is a C1-C5 alkylene group.

[0016] As a further improvement of the present invention, the resin composition further comprises 1-60 parts by weight of anhydride copolymer; and / or, 5-50 parts by weight of epoxy resin; and / or, 5-60 parts by weight of elastomer; and / or, 5-30 parts by weight of flame retardant.

[0017] As a further improvement of the present invention, the resin composition further comprises 1-60 parts by weight of an anhydride copolymer, wherein the anhydride copolymer is at least one of a styrene-maleic anhydride copolymer and a styrene-maleic anhydride-maleimide copolymer.

[0018] As a further improvement of the present invention, the maleimide resin is selected from at least one of the following structural formulas:

[0019]

[0020]

[0021] R2 is hydrogen, methyl or ethyl, R1 is methylene, ethylene or n is an integer from 1 to 10;

[0022]

[0023] n is an integer from 1 to 10;

[0024] n is an integer from 1 to 10;

[0025] R is hydrogen, methyl or ethyl, and n is an integer of 1-10.

[0026] To achieve the above-mentioned object of the invention, the present invention also provides a use of the above-mentioned resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0027] Beneficial effects: Compared with the prior art, the present invention has the following advantages:

[0028] A first filler with high Dk (dielectric constant) and a second filler with high thermal conductivity are added to the resin composition of the present invention, that is, the first filler with high Dk and the second filler with high thermal conductivity are used in combination, and the first filler and the second filler are surface treated with an anhydride-based silane coupling agent, which can improve the compatibility between the first filler, the second filler and the maleimide resin, while maintaining high heat resistance and adhesion, and obtain a cured product with excellent high heat resistance, high adhesion, high thermal conductivity and a stable high Dk value, that is, a cured product with relatively excellent comprehensive performance is obtained, which meets the requirements of high heat resistance, high adhesion, high Dk and high thermal conductivity of the 5G millimeter wave antenna module. DETAILED DESCRIPTION

[0029] The following is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0030] The terms “comprising” and “containing” in the present specification mean that other components may be contained in addition to the components mentioned above, and these other components can impart different characteristics to the resin composition.

[0031] The present invention provides a resin composition, comprising:

[0032] Maleimide resin: 50-100 parts by weight;

[0033] First filler: 10-80 parts by weight, wherein the first filler is a titanate compound;

[0034] Second filler: 10-100 parts by weight, the second filler is at least one of aluminum nitride, silicon nitride or boron nitride;

[0035] The first filler and / or the second filler are surface treated with an anhydride-based silane coupling agent.

[0036] A first filler with high Dk (dielectric constant) and a second filler with high thermal conductivity are added to the resin composition of the present invention, that is, the first filler with high Dk and the second filler with high thermal conductivity are used in combination, and the first filler and the second filler are surface treated with an anhydride-based silane coupling agent, which can improve the compatibility between the first filler, the second filler and the maleimide resin, while maintaining high heat resistance and adhesion, and obtain a cured product with excellent high heat resistance, high adhesion, high thermal conductivity and a stable high Dk value, that is, a cured product with relatively excellent comprehensive performance is obtained, which meets the requirements of high heat resistance, high adhesion, high Dk and high thermal conductivity of the 5G millimeter wave antenna module.

[0037] It should be noted that the cured product in the present invention can be understood as a prepreg, an insulating film, an insulating board, a copper-clad laminate, a circuit substrate, an electronic device, and the like.

[0038] Specifically, the titanate compound is at least one of calcium titanate, barium titanate, strontium titanate, lead titanate, magnesium titanate, lanthanum titanate, neodymium titanate, barium neodymium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

[0039] Preferably, the first filler is selected from at least one of barium titanate, strontium titanate or calcium titanate.

[0040] In a specific embodiment, the first filler is selected from calcium titanate CT-3, calcium titanate ST-2, strontium titanate SBT-K3 or strontium titanate BT-HP9DX manufactured by Kyoritsu Materials, strontium titanate SW-100, strontium titanate SW-50C, strontium titanate SW-100C, strontium titanate SW-200C, strontium titanate SW-320C or strontium titanate SW-350 manufactured by Titanium Industry, strontium titanate ST, strontium titanate ST-S1, strontium titanate HST-1, strontium titanate HPST-1 or strontium titanate HPST-2 manufactured by Fuji Titanium Industry, and barium titanate BT-149 manufactured by Nippon Chemical Industry.

[0041] In a specific embodiment, the second filler is selected from boron nitride SP3-7 or boron nitride SGP manufactured by DENKA, aluminum nitride FAN-f30 or aluminum nitride FAN-f-50 manufactured by Furukawa Electronics, boron nitride HP-40, boron nitride HP-40MF or boron nitride HP40-J2 manufactured by Mizushima Alloy, boron nitride MBN-010T manufactured by Mitsui Chemicals, and silicon nitride SN-1040 manufactured by Lianrui New Materials.

[0042] In some optional embodiments, the weight ratio of the first filler to the second filler is 0.3-5, such as 0.3, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 4.8, 4.5, 5 and specific point values ​​between the above values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0043] Preferably, the weight ratio of the first filler to the second filler is 0.5-2, such as 0.5, 0.8, 1, 1.3, 1.5, 1.8, 2 and specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0044] Specifically, the average particle size of the first filler is 0.1-5μm, such as 0.1μm, 1μm, 2μm, 3μm, 4μm, 5μm and specific point values ​​between the above-mentioned values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range; the average particle size of the second filler is 3-20μm, such as 3μm, 5μm, 10μm, 15μm, 20μm and specific point values ​​between the above-mentioned values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0045] In a preferred embodiment, the average particle size of the second filler is larger than the average particle size of the first filler, that is, the average particle size of the high thermal conductive second filler is larger than the average particle size of the high Dk first filler. In the resin composition, the high Dk filler with smaller particle size will be dispersed into the high thermal conductive fillers with larger particle size, which can improve the thermal conductivity of the substrate. At the same time, the high Dk filler with smaller particle size is evenly dispersed, maintaining a high thermal conductivity while suppressing the decrease in the Dk value of the resin composition, thereby obtaining a resin composition with high thermal conductivity and a high level of Dk value. It is also possible to increase the filling amount of the filler in the resin composition and maintain the excellent dispersibility of the filler, so that the resin composition has excellent high dielectric constant and high thermal conductivity, and obtain a cured product with excellent high heat resistance, high adhesion, high thermal conductivity and stable high Dk value, that is, a cured product with relatively excellent comprehensive performance, which meets the requirements of high heat resistance, high adhesion, high Dk and high thermal conductivity of the 5G millimeter wave antenna module.

[0046] Specifically, the average particle size of the first filler is 0.1-2μm, such as 0.1μm, 1μm, 2μm and specific point values ​​between the above-mentioned values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range; the average particle size of the second filler is 3-10μm, such as 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm and specific point values ​​between the above-mentioned values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0047] In some optional embodiments, the structural formula of the anhydride-based silane coupling agent is:

[0048] Among them, the R group is a C1-C5 alkyl group, and R1 is a C1-C5 alkylene group.

[0049] In the present invention, the first filler and the second filler treated with the surface of the anhydride-containing silane coupling agent exhibit excellent dispersibility in the maleimide resin system. This is because the anhydride group and the maleimide in the silane coupling agent are both five-membered ring structures, and the two have similar structures. The high-content inorganic filler can be evenly dispersed in the matrix resin to obtain a cured product with excellent comprehensive performance.

[0050] In some preferred embodiments, the R group in the structural formula of the above-mentioned anhydride-based silane coupling agent is a methyl group or an ethyl group, and the R1 group is an ethylene group or a propylene group.

[0051] Specifically, the surface treatment method of the anhydride-based silane coupling agent for the first filler and the second filler can be a physical method or a chemical method, such as a dry method, an adsorption method, a chemical reaction method, a polymerization method, a gas phase surface treatment method, etc., which are not specifically described here.

[0052] In some optional embodiments, the resin composition further includes 1-60 parts by weight of anhydride copolymer, such as 1 part by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight and specific point values ​​between the above values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0053] When an anhydride copolymer is added to the resin composition, the anhydride groups on the surface of the first filler and the second filler, the maleimide groups in the maleimide resin and the anhydride groups in the anhydride copolymer are all five-membered ring structures, which can be well matched with each other, and a very homogeneous resin composition glue can be obtained. Even if a higher content of the first filler and the second filler is added to the resin composition, good processability can be maintained and high adhesion can be achieved.

[0054] Specifically, the anhydride copolymer optionally contains the following structural units:

[0055] The Ar group is a C1-C5 alkyl group, a phenyl group or a naphthyl group.

[0056] In one specific embodiment, the anhydride copolymer is a styrene-maleic anhydride copolymer, that is, the anhydride copolymer contains a structural unit Wherein, the molar ratio of n:m is (1-10):1.

[0057] In another specific embodiment, the anhydride copolymer is a styrene-maleic anhydride-maleimide copolymer, that is, the anhydride copolymer contains a structural unit The molar ratio of n:m:k is (1-10):(1-5):(1-10).

[0058] In some optional embodiments, the maleimide resin is a modified maleimide resin. When the modified maleimide resin is used, the compatibility with other thermosetting resins is better.

[0059] Preferably, the modified maleimide resin is at least one of allyl-modified maleimide prepolymer, diamine-modified maleimide prepolymer and aminophenol-modified maleimide prepolymer.

[0060] Specifically, the allyl compound in the allyl-modified maleimide prepolymer is at least one selected from diallyl bisphenol A, diallyl bisphenol S, allyl phenoloxy resin, allyl phenol formaldehyde resin and diallyl diphenyl ether.

[0061] The diamine compound in the diamine-modified maleimide prepolymer is selected from at least one of unsubstituted phenylenediamine, methylphenylenediamine, dimethylphenylenediamine, trimethylphenylenediamine, tetramethylphenylenediamine, xylene diamine, diaminopyridine, diaminodiphenylmethane, substituted diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, diaminobenzophenone, diaminodiphenyl ether, diaminodiphenyl sulfone, diaminobiphenyl, diaminodiphenyl sulfide, diaminobinaphthyl, diaminodiphenylfluorene, and diaminoanthraquinone.

[0062] Preferably, the aromatic amine compound is selected from at least one of diaminodiphenyl sulfone, diaminodiphenyl ether and diaminodiphenylmethane.

[0063] Preferably, the maleimide resin is selected from at least one of the following structural formulas:

[0064]

[0065] R2 is hydrogen, methyl or ethyl, R1 is methylene, ethylene or n is an integer from 1 to 10;

[0066]

[0067] n is an integer from 1 to 10;

[0068] n is an integer from 1 to 10;

[0069] R is hydrogen, methyl or ethyl, and n is an integer of 1-10.

[0070] Specifically, the maleimide resin is selected from any one or more of the following brands of materials: BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000H, BMI-5000, BMI-5100, BMI-7000, BMI-7000H manufactured by Yamato Chemical Industry Co., Ltd.; BMI, BMI-70, BMI-80 manufactured by KI Chemical Industry Co., Ltd. of Japan; MIR-3000, MIR-5000 manufactured by Nippon Kayaku Co., Ltd.; X9-450, X9-470 manufactured by DIC Corporation of Japan; D936, D937, D939, D950 manufactured by Sichuan Dongcai Co., Ltd.

[0071] In some optional embodiments, the resin composition further comprises 5-50 parts by weight of epoxy resin. Although the Tg of the resin composition is reduced, the overall processability is better.

[0072] The epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, naphthalene-type epoxy resin, phosphorus-containing epoxy resin, o-cresol epoxy resin, bisphenol A novolac epoxy resin, phenol novolac epoxy resin, trifunctional phenol-type epoxy resin, tetraphenylethane epoxy resin, biphenyl-type epoxy resin, dicyclopentadiene-type epoxy resin, isocyanate-type epoxy resin, aralkyl linear novolac epoxy resin, alicyclic epoxy resin, glycidylamine-type epoxy resin, and glycidylester-type epoxy resin.

[0073] Specifically, the epoxy resin can be selected from any one or more of the following brand materials: HP4032, HP4032H, HP4032D, HP4032SS, HP4700, HP4710, N-690, N-695, HP7200, HP7200H, HP7200HH, EXA7311, HP6000 made by DIC, NC3000, NC7000, NC3100 made by Nippon Kayaku, ESN475V, ESN485 made by Nippon Steel Chemical.

[0074] In some optional embodiments, the resin composition further comprises 5-60 parts by weight of an elastomer. When an appropriate amount of elastomer is added to the resin composition, it cooperates with a high content of inorganic fillers (first filler, second filler) to further improve toughness and thermal expansion coefficient on the basis of meeting higher thermal conductivity and dielectric constant.

[0075] The elastomer is selected from at least one of styrene elastomers, silicone elastomers and methacrylate elastomers.

[0076] Specifically, the styrene-based elastomer is at least one of a hydrogenated styrene and butadiene diblock copolymer, a hydrogenated styrene and butadiene triblock copolymer, a hydrogenated styrene and pentadiene diblock copolymer, and a hydrogenated styrene and pentadiene triblock copolymer.

[0077] The silicone-based elastomer contains at least one structural unit of structural formula (9), structural formula (10) and structural formula (11):

[0078] In the structural formula (9), R is C1-C 12 The hydrocarbon group or -OR;

[0079] In the structural formula (10), R is C1-C 12 The hydrocarbon group or -OR;

[0080] In the structural formula (11), X is a mercapto group, an epoxy group, a hydroxyl group or a methoxy group.

[0081] The methacrylate elastomer contains the following structural formula (12) and / or structural formula (13):

[0082] In the structural formula (12), R1 is a C1-C5 alkyl group, and x is an integer of 1 to 100;

[0083] In the structural formula (13), R2 is a C1-C5 alkyl group, and y is an integer of 1-100.

[0084] In some optional embodiments, the resin composition further comprises 0.01-8 parts by weight of a catalyst, wherein the catalyst is at least one selected from imidazoles, pyridines, organic phosphorus or metal salts.

[0085] Preferably, the imidazole catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole and zinc octanoate.

[0086] Preferably, the organophosphorus is selected from triphenylphosphine.

[0087] Furthermore, the resin composition also includes 5-30 parts by weight of a flame retardant, so that the final cured product has a certain flame retardant effect.

[0088] The flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organic silicon flame retardant, and an organic metal salt flame retardant.

[0089] Specifically, the bromine flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide. The phosphorus flame retardant is selected from inorganic phosphorus, condensed phosphate ester, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene.

[0090] Among them, the DOPO group in the above structure is

[0091] In a preferred embodiment, the flame retardant is a condensed phosphate ester, a hypophosphite or a bis-DOPO compound.

[0092] Furthermore, the present invention also provides a use of the above resin composition in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

[0093] Specifically, the present invention further provides a prepreg, which comprises a reinforcing material and the above-mentioned resin composition, wherein the resin composition is impregnated on the reinforcing material.

[0094] The reinforcing material may be selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics.

[0095] Preferably, the reinforcing material is glass fiber cloth. Among the glass fiber cloth, open fiber cloth or flat cloth is preferably used. More preferably, the glass fiber cloth is E glass fiber cloth, S glass fiber cloth, T glass fiber cloth or Q glass fiber cloth.

[0096] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth generally needs to be chemically treated to improve the interface bonding between the resin composition and the glass fiber cloth. The main method of the chemical treatment is coupling agent treatment, and the coupling agent used is preferably epoxy silane coupling agent or amino silane coupling agent, so that the reinforcing material has good water resistance and heat resistance.

[0097] Specifically, the method for preparing the prepreg comprises the following steps:

[0098] Dissolving the resin composition with a solvent to prepare a resin composition glue solution;

[0099] The reinforcing material is immersed in the above-mentioned resin composition glue solution, and then the immersed reinforcing material is taken out and heated and dried to obtain the prepreg.

[0100] In a specific embodiment, the impregnated reinforcing material is baked at 100° C. to 180° C. for 1 min to 15 min, and the prepreg is obtained after drying.

[0101] Specifically, the solvent can be selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.

[0102] The present invention does not specifically limit the amount of solvent used in preparing the prepreg. The amount of solvent added is selected by those skilled in the art based on their own experience, as long as the obtained resin composition glue has a viscosity suitable for use.

[0103] The present invention also provides a copper-clad laminate, which comprises at least one of the above-mentioned prepregs and a metal foil formed on at least one side of the prepreg. When the copper-clad laminate comprises only one of the above-mentioned prepregs, the metal foil is arranged on at least one side of the surface of the prepreg. When the copper-clad laminate comprises at least two of the above-mentioned prepregs, the at least two prepregs are stacked and bonded together by heating and pressurizing to form a combined sheet, and then the metal foil is bonded on one side or both sides of the combined sheet by heating and pressurizing to form the copper-clad laminate.

[0104] Specifically, the preparation steps of the copper-clad laminate are as follows: a single side or double sides of a prepreg is coated with metal foil, or at least two prepregs are stacked to form a combined sheet, a single side or double sides of the combined sheet is coated with metal foil, and hot pressing is performed to obtain a copper-clad laminate.

[0105] The pressing conditions of the copper-clad laminate are: pressing at a pressure of 0.2 to 2 MPa and a temperature of 150° C. to 250° C. for 1 to 4 hours.

[0106] Specifically, the number of the prepregs can be determined according to the required thickness of the copper-clad laminate, and one or more prepregs can be used.

[0107] The metal foil may be copper foil or aluminum foil, and its material is not limited; the thickness of the metal foil is not particularly limited, such as 5 μm, 8 μm, 12 μm, 18 μm, 35 μm or 70 μm.

[0108] The present invention also provides an insulating plate, which comprises at least one of the aforementioned prepreg sheets.

[0109] The present invention also provides an insulating film, which comprises a carrier film and the aforementioned resin composition coated thereon, and can significantly improve the heat resistance of the insulating film.

[0110] The preparation method of the insulating film is as follows: dissolving the resin composition with a solvent to prepare a resin composition glue solution, then coating the resin composition glue solution on a carrier film, and heating and drying the carrier film coated with the resin composition glue solution to obtain the insulating film.

[0111] In a specific embodiment, the carrier film coated with the resin composition glue is baked at 100° C. to 160° C. for 3 min to 10 min, and the insulating film can be obtained after drying.

[0112] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.

[0113] The carrier film is selected from at least one of PET film, PP film, PE film and PVC film.

[0114] The present invention also provides a circuit substrate, which includes one or more of the aforementioned prepreg, copper-clad laminate, insulating plate, and insulating film.

[0115] The present invention also provides an electronic device, which includes the aforementioned circuit substrate.

[0116] The present invention will be described in detail below with specific examples and comparative examples; of course, it can be understood that the embodiments of the present invention are not limited to these examples.

[0117] Examples 1 to 5 and Comparative Examples 1 to 2:

[0118] The components and contents of the resin compositions of Examples 1 to 5 and Comparative Examples 1 to 2 are shown in Table 1 below:

[0119] Table 1

[0120]

[0121] Specifically, the information of each component involved in Table 1 above is shown in Table 2 below:

[0122] Table 2

[0123]

[0124]

[0125] The preparation method of the resin composition in Examples 1 to 5 and Comparative Examples 1 to 2 is as follows: according to the components and corresponding contents in Table 1, an appropriate amount of butanone is mixed, stirred and mixed, and then diluted to a resin composition glue having a solid content of 65wt%, wherein the solid content of 65wt% is calculated by weight.

[0126] The E glass fiber cloth 7628 used as a reinforcing material was pretreated with an epoxy silane coupling agent and then immersed in the resin composition glue obtained in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 2, taken out after being soaked, placed in a 160° C. forced drying oven, and baked for 3 to 6 minutes to obtain the semi-cured sheets corresponding to Examples 1 to 5 and Comparative Examples 1 to 2, respectively.

[0127] Copper-clad laminates corresponding to the above-mentioned embodiments 1 to 5 and comparative examples 1 to 2 were prepared. The method for preparing the copper-clad laminate was as follows: two semi-cured sheets prepared as above were cut to 300×300 mm, and the two semi-cured sheets were stacked into a composite sheet with a certain stacking structure, and then a low-profile electrolytic copper foil with a thickness of 12 μm was placed on both sides of the composite sheet, and then placed in a vacuum hot press, and hot pressed for 1.5 hours at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate.

[0128] The copper-clad laminates corresponding to the above-mentioned embodiments 1 to 5 and comparative examples 1 to 2 were used for performance testing. Specifically, the performance evaluation method is as follows:

[0129] (1) Glass transition temperature (Tg): tested using a dynamic mechanical analyzer (DMA) according to IPC-TM-650 2.4.24.4;

[0130] (2) Thermal conductivity: tested using ASTM D5470-2017 method;

[0131] (3) Dk and Df: Dielectric properties at 10 GHz were measured using the plate method in accordance with IPC-TM-650 2.5.5.9;

[0132] (4) Dk and Df after moisture absorption: After being treated at 85% RH and 85°C for 10 days, the test was performed again according to IPC-TM-6502.5.5.9.

[0133] The properties of the copper-clad laminates obtained using the prepregs in Examples 1 to 5 and Comparative Examples 1 to 2 are shown in Table 3 below.

[0134] Table 3

[0135]

[0136] Example 1 and Comparative Example 1 are compared in parallel. Conventional silica filler is used in the resin composition in Comparative Example 1, and high Dk strontium titanate and high thermal conductivity silicon nitride filler are used in Example 1. At the same time, strontium titanate and silicon nitride are surface treated with an anhydride-based silane coupling agent. Comparing the performance of the copper-clad laminate corresponding to Example 1 with the performance of the copper-clad laminate corresponding to Comparative Example 1, it can be seen that the copper-clad laminate prepared from the resin composition in Example 1 has a higher dielectric constant Dk, higher thermal conductivity, and lower dielectric loss Df, which meets the requirements of high heat resistance, high Dk, low dielectric loss Df and high thermal conductivity of the 5G millimeter wave antenna module.

[0137] Example 2 and Comparative Example 2 are compared in parallel. The high Dk calcium titanate filler and the high thermal conductivity silicon nitride filler in the resin composition of Comparative Example 2 are not surface treated, while the calcium titanate and silicon nitride in Example 2 are surface treated with an anhydride-based silane coupling agent. Comparing the performance of the copper-clad laminate corresponding to Example 2 with the performance of the copper-clad laminate corresponding to Comparative Example 2, it can be seen that the copper-clad laminate prepared from the resin composition in Example 2 has a higher dielectric constant Dk, a higher thermal conductivity, and a lower dielectric loss Df, meeting the requirements of high heat resistance, high Dk, low dielectric loss Df, and high thermal conductivity of the 5G millimeter wave antenna module.

[0138] It can be seen that the resin composition of the present invention adds a first filler with high Dk (dielectric constant) and a second filler with high thermal conductivity, that is, the first filler with high Dk and the second filler with high thermal conductivity are used in combination, and the first filler and the second filler are surface-treated with anhydride-based silane coupling agent, which can improve the compatibility between the first filler, the second filler and the maleimide resin, while maintaining high heat resistance and adhesion, and obtain a cured product with excellent high heat resistance, high adhesion, high thermal conductivity and a stable high Dk value, that is, a cured product with relatively excellent comprehensive performance is obtained, which meets the requirements of high heat resistance, high adhesion, high Dk and high thermal conductivity of the 5G millimeter wave antenna module.

[0139] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0140] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A resin composition, characterized in that include: Maleimide resin: 50-100 parts by weight; First filler: 10-80 parts by weight, wherein the first filler is a titanate compound; Second filler: 10-100 parts by weight, the second filler is at least one of aluminum nitride, silicon nitride or boron nitride; The first filler and / or the second filler are surface treated with an anhydride-based silane coupling agent.

2. The resin composition according to claim 1, characterized in that: The weight ratio of the first filler to the second filler is 0.3-5.

3. The resin composition according to claim 1, characterized in that: The first filler is at least one of calcium titanate, barium titanate, strontium titanate, lead titanate, magnesium titanate, lanthanum titanate, neodymium titanate, barium neodymium titanate, lead zirconate titanate, and lanthanum lead zirconate titanate.

4. The resin composition according to claim 1, characterized in that: The average particle size of the first filler is 0.1-5 μm, and the average particle size of the second filler is 3-20 μm.

5. The resin composition according to claim 4, characterized in that: The average particle size of the second filler is greater than the average particle size of the first filler.

6. The resin composition according to claim 1, characterized in that: The structural formula of the anhydride-based silane coupling agent is: Among them, the R group is a C1-C5 alkyl group, and R1 is a C1-C5 alkylene group.

7. The resin composition according to claim 1, characterized in that: The resin composition further comprises 1-60 parts by weight of anhydride copolymer; and / or, 5-50 parts by weight of epoxy resin; and / or, 5-60 parts by weight of elastomer; and / or, 5-30 parts by weight of flame retardant.

8. The resin composition according to claim 7, characterized in that: The resin composition further comprises 1-60 parts by weight of an anhydride copolymer, wherein the anhydride copolymer is at least one of a styrene-maleic anhydride copolymer and a styrene-maleic anhydride-maleimide copolymer.

9. The resin composition according to claim 1, characterized in that: The maleimide resin is selected from at least one of the following structural formulas: R2 is hydrogen, methyl or ethyl, R1 is methylene, ethylene or n is an integer from 1 to 10; n is an integer from 1 to 10; n is an integer from 1 to 10; R is hydrogen, methyl or ethyl, and n is an integer of 1-10.

10. Use of the resin composition according to any one of claims 1 to 9 in prepregs, copper-clad laminates, insulating films, insulating boards, circuit substrates and electronic devices.

Citation Information

Patent Citations

  • Thermosetting resin composition, prepreg, metal foil-coated laminate, and printed circuit board

    CN106916418A

  • Resin composition and product thereof

    CN115678247A

  • Resin composition, prepreg, resin sheet, laminate, metal foil-clad laminate, and printed wiring board

    CN116457417A

  • Resin composition and application thereof

    CN116875053A

  • Resin composition

    CN117343474A

Cited By

  • Resin composition and application thereof

    WO2026086083A1